Elucidating the pathogenicity, diagnosis, treatment, and prevention of COVID-19: Part I - Monisha Parshotam Khatri; Sekar Mahalaxmi (Wolters Kluwer Medknow Publications, 2022)
Background: From the beginning of 2020, much and more has been spoken about the coronavirus and coronavirus disease-19 (COVID-19). The concepts in terms of the infection, its transmission, the treatment, and its prevention are ever changing as well as unclear. Aim: The Part I of this review article strived to provide a clear picture on the pathogenesis, diagnosis, and treatment of COVID-19. Methods: An electronic search was performed in PubMed and Google Scholar database with the keywords "Corona Virus, COVID 19, World Health Organization, Severe Acute Respiratory Syndrome (SARS), SARS-CoV-2, Pathogenesis, Diagnosis, Treatment, Plasma Convalescent Therapy, Immune system" from January 2017 to December 2021. Results: A total of 65 articles were included in the current review and analyzed to simplify the complicated information available in the literature. Conclusion: COVID-19 as said to originate from bats and transmitted through intermediatory hosts like pangolins, can be diagnosed symptomatically and with tests such as blood investigation, reverse transcription-polymerase chain reaction, computed tomography scan, saliva, or gingival crevicular fluid. Various treatment options include use of drugs such as antivirals, antimalarial, immune enhancers, nonsteroidal anti-inflammatory drugs, corticosteroids, anticoagulant therapy, and antibodies.